2021
DOI: 10.3748/wjg.v27.i30.4985
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and liver disease in a developing country

Abstract: Malnutrition is a highly prevalent and under recognized condition in developing countries of South Asia. The presence of malnutrition causes a severe impact on patients with liver cirrhosis. The etiology of cirrhosis differs in the South Asian region compared to the West, with hepatitis B and C still being the leading causes and the prevalence of nonalcoholic fatty liver disease increasing over time. Comorbid malnutrition worsens outcomes for cirrhosis patients. Urgent attention to address malnutrition is need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 90 publications
0
3
0
1
Order By: Relevance
“…In the South Asian area, the causes of cirrhosis are different from those in the West. Hepatitis B and C remain the main causes, although the frequency of nonalcoholic fatty liver disease is growing over time [1]. Coexisting malnutrition exacerbates outcomes for people with hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…In the South Asian area, the causes of cirrhosis are different from those in the West. Hepatitis B and C remain the main causes, although the frequency of nonalcoholic fatty liver disease is growing over time [1]. Coexisting malnutrition exacerbates outcomes for people with hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is a condition in which the intake or absorption of nutrients essential for development and the prevention of disease is inadequate [ 1 , 2 ]. Compared to healthy individuals, patients with gastrointestinal diseases often have altered nutrient metabolism [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study revealed that only 20% of gastroenterologists correctly identified the prevalence of malnutrition in patients with liver cirrhosis, indicating the knowledge gap (6). Due to the decline in health caused by cirrhosis, an estimated one million people die from cirrhosis worldwide, making it a significant disease burden that must be addressed (7). Malnutrition is aligned with life-threatening complications like refractory ascites, spontaneous bacterial peritonitis, hepatorenal syndrome, and variceal bleeding.…”
Section: Introductionmentioning
confidence: 99%